2019
DOI: 10.1186/s40795-019-0311-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D supplementation on the glycemic control of pre-diabetic Qatari patients in a randomized control trial

Abstract: Background: Vitamin D deficiency is associated with indicators of pre-diabetes including, insulin resistance, β-cell dysfunction and elevated plasma glucose with controversial findings from current trials. This study aims to investigate the long-term effect of vitamin D on glucose metabolism and insulin sensitivity in pre-diabetic and highly vitamindeficient subjects. Methods: One hundred thirty-two participants were randomized to 30,000 IU vitamin D weekly for 6 months. Participants underwent oral glucose tol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The discrepancy could be due to the cohort difference, including age, ethnicity, and eating habit. However, our results are in line with the failure in clinical trials of vitamin D supplements for improving glucose tolerance and insulin sensitivity 36 . By analyzing multiple anthropometric and biochemical measures, we rank them by their ability to predict T2D according to the ROC-AUC values: in women, age (0.75) > waist circumference (0.70) > systolic pressure (0.66) = triglyceride (0.66) = fasting proinsulin (0.66) > fasting insulin (0.64) > total cholesterol (0.63) > BMI (0.62) = LDL (0.62) > LDL (0.62) > diastolic pressure (0.60); in men, age (0.69) > fasting proinsulin (0.62) > fasting P/I ratio (0.61).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The discrepancy could be due to the cohort difference, including age, ethnicity, and eating habit. However, our results are in line with the failure in clinical trials of vitamin D supplements for improving glucose tolerance and insulin sensitivity 36 . By analyzing multiple anthropometric and biochemical measures, we rank them by their ability to predict T2D according to the ROC-AUC values: in women, age (0.75) > waist circumference (0.70) > systolic pressure (0.66) = triglyceride (0.66) = fasting proinsulin (0.66) > fasting insulin (0.64) > total cholesterol (0.63) > BMI (0.62) = LDL (0.62) > LDL (0.62) > diastolic pressure (0.60); in men, age (0.69) > fasting proinsulin (0.62) > fasting P/I ratio (0.61).…”
Section: Discussionsupporting
confidence: 85%
“…The discrepancy could be due to the cohort difference, including age, ethnicity, and eating habit. However, our results are in line with the failure in clinical trials of vitamin D supplements for improving glucose tolerance and insulin sensitivity 36 .…”
Section: Discussionsupporting
confidence: 85%
“…[ 21 ] In another study conducted by Harris et al .,[ 22 ] it was observed that Insulin sensitivity decreased by 4% in the intervention (Vit D group) while it increased by 12% in the control group ( P = 0.034). Whereas in other studies[ 23 24 25 26 ] there was no significant effect of vitamin D on insulin sensitivity.…”
Section: Discussionmentioning
confidence: 66%
“…The change in BMI after vitamin D intervention was reported in 23 studies (N = 2854) [12,14,17,18,[20][21][22][23][25][26][27][28][29][30][31][32][33][34][35][36][37]39,40]. Random-effects meta-analysis showed no difference in BMI changes between vitamin D supplementation and controls (SMD = 0.01; 95%CI: −0.22, 0.24; p = 0.935) (Figure S2), while the results showed statistically significant heterogeneity (I 2 = 88.7%, p < 0.001).…”
Section: Bmimentioning
confidence: 99%
“…Twenty-five trials involving 3144 participants were included to demonstrate the effect of vitamin D supplementation on FBG in prediabetics [12][13][14][15][16][17][18][19][20][21]23,26,27,[29][30][31][32][33][34][35][36][37][38][39][40]. Overall, a significant decrease in FBG content was observed in the vitamin D supplementation group (SMD = −0.38; 95%CI: −0.59, −0.16; p = 0.001) (Figure 2), with a high heterogeneity (I 2 = 87.6%, p < 0.001).…”
Section: Fbgmentioning
confidence: 99%